Are Power Utilities in Tonga and New Zealand Resilient? : Human and Organizational Factors in Disaster Response - Brown, Ray; Wang, Xiaoping; Page, Christopher (2016)
Given the increasing frequency and severity of extreme weather events, it is useful to understand the lessons learned from recent natural disasters in Ha’apai, Tonga, and Christchurch, New Zealand. Despite vastly different circumstances, the two experiences demonstrate that power outages can be shortened through access to adequate human resources, immediate and frequent communication with the public, good pre-disaster maintenance, and standardized equipment. By attending to these factors, utilities can become more resilient and help communities recover more quickly.